Koshi Tappu Ramsar Site: Updates on Ramsar Information Sheet on Wetlands - Karki, Jhamak B (The Initiation, 2010)
Major changes to the ecological character of the Ramsar site, including in the application of the Criteria, since the previous Ramsar Information Sheet (RIS) for the site are the degradation of forest quality due to the invasion of the exotic species especially Mikania micrantha since last few years, replacement of old grassland habitat by new ones due to the meandering of the Koshi River and alteration of plant species composition due to the vegetation changes. For example, few plant species have appeared in the Sisso- Acacia forest habitat. Decline in water birds population due to poisoning, siltation in the rivers/surrounding wetlands and over fishing has been noticed. Moreover eutrophication is prevalent in most stagnant waters especially oxbow lakes and seepage ponds. Over-exploitation in the natural resources has led to the degradation of the habitat quality and loss, hence the change in population of Wild Water Buffalo (Bubalus arnee), deer species (Axis spp.), Gharial (Gavialis gangeticus) and Gangetic Dolphin (Platanista gangetica). The current flood of Koshi River after the breakage of the eastern embankment is uncertain to predict the future of the lower part of the Koshi Tappu Ramsar site. Key Words: Ramsar information sheet (RIS), Alien spps, Koshi tappu wildlife reserve (KTWR), Ramsar convention. DOI: 10.3126/init.v2i1.2513 The Initiation Vol.2(1) pp10-16